2018
DOI: 10.1186/s12906-018-2089-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of active constituents from bark of Ficus racemosa L in wound healing

Abstract: BackgroundDifferent parts including the latex of Ficus racemosa L. has been used as a medicine for wound healing in the Ayurveda and in the indigenous system of medicine in Sri Lanka. This plant has been evaluated for its wound healing potential using animal models. The aim of this study was to obtain an insight into the wound healing process and identify the potential wound healing active substance/s present in F. racemosa L. bark using scratch wound assay (SWA) as the in-vitro assay method.MethodStem bark ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…They include P. granatum, P. guajava, C. arborea, G. decora, S. obtusa, and F. hispida. The findings about the potential effectiveness of these plants are similar to those found in the in vivo and in vitro studies previously reported [31][32][33][34][35][36][37][38][39][40]. Leaves from P. granatum and P. guajava and pieces of bark from C. arborea, G. decora, S. obtusa, and F. hispida were collected in Baan Tham, Dok Kham Tai, Phayao.…”
Section: Collection and Preparation Of The Extractssupporting
confidence: 82%
“…They include P. granatum, P. guajava, C. arborea, G. decora, S. obtusa, and F. hispida. The findings about the potential effectiveness of these plants are similar to those found in the in vivo and in vitro studies previously reported [31][32][33][34][35][36][37][38][39][40]. Leaves from P. granatum and P. guajava and pieces of bark from C. arborea, G. decora, S. obtusa, and F. hispida were collected in Baan Tham, Dok Kham Tai, Phayao.…”
Section: Collection and Preparation Of The Extractssupporting
confidence: 82%
“…These results corresponded to the previous Ficus reports that showed bioactivities involving their lupeol profiles. [22][23][24] Although a direct correlation between the cytotoxic performance and lupeol content was observed in the extracted samples of F. racemosa and C. indicum, it was inverse in the extract of T. triandra, which possessed the highest cytotoxic potency in this study. The capability on cytotoxicity of T. triandra might correspond with prominent cytotoxic alkaloids, i.e.…”
Section: Discussioncontrasting
confidence: 55%
“…SWA was performed as described previously [ 27 ]. Briefly, cells (2 × 10 4 ) were incubated at 37 °C for 24 h. A scratch (wound) was performed on monolayer of cells along the vertical axis of each well under a light microscope.…”
Section: Methodsmentioning
confidence: 99%